EPA and DHA Exposure Alters the Inflammatory Response but not the Surface Expression of Toll‐like Receptor 4 in Macrophages. Issue 2 (19th November 2014) - Honda, Kaori L.; Lamon‐Fava, Stefania; Matthan, Nirupa R.; Wu, Dayong; Lichtenstein, Alice H.
Abstract: Dietary intake of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) and their respective enrichment in cell membranes have been negatively associated with atherosclerotic lesion development. This effect may be mediated, in part, by dampened inflammatory response of macrophages triggered by toll‐like receptor 4 (TLR4) activation. This study investigated the influence of membrane fatty acid profile on TLR4‐mediated inflammation in RAW 264.7 macrophages. Cells pretreated with myristic acid (MA), EPA, DHA or vehicle control for 24 h were stimulated with ultra‐pure LPS, a specific TLR4 agonist, for 6 or 24 h, corresponding to early and late stages of TNFα and IL‐6 protein induction. Treatment significantly increased cell membrane MA, EPA, and DHA by 4.5‐, 20.6‐, and 8.9‐fold, respectively. MA significantly increased IL‐6 secretion 6 h post‐exposure to the fatty acid, but did not change TNFα secretion in response to any other treatment condition. EPA and DHA significantly reduced TNFα secretion by 36 and 41 %, respectively, in cells stimulated for 24 h but not 6 h. In contrast, EPA and DHA significantly reduced IL‐6 secretion at both 6 h (67 and 72 %, respectively) and 24 h (69 and 72 %, respectively). MA or DHA treatment had no significant effect compared to vehicle on factors influencing cellular LPS recognition, including LPS‐cell association, and cell surface expression of TLR4, TLR4‐MD2 complex, and CD14. These data suggest that membrane fatty acid profiles influence the TLR4‐mediated inflammatory response in macrophages, via mechanisms that occur downstream of TLR4 receptor activation.